Exemplary leadership practices in early childhood education in preparing the golden generations for Indonesia - Usnul Umi Miftahurrohmah; Hasan Hariri; Riswanti Rini; Rohmatillah Rohmatillah (Goodwood Publishing, 2021)
Purpose: This study aimed to investigate the ideal quality of inclusive early childhood education, an effective leadership style and five practices of exemplary leadership. Research methodology: This is a review article. The review process began with a search engine (Google Scholar) to search and review early childhood education and leadership articles. Results: The results suggest that it is important to hold quality inclusive early childhood educations since, in this level of education, six developmental areas are well stimulated. The key success of maintaining quality inclusive early childhood education is a collaboration among education parties (government, school, parents and community). A school needs a principal who can perform five exemplary leadership practices to help “Golden Indonesia 2045” become true. Limitations: First, the scope of articles reviewed is still very limited to the literature review in the Indonesian context. This and other limitations will be opportunities for further empirical studies about five practices of exemplary leadership in the Indonesian education area. Contribution: This study can be useful for the early childhood education level.